A Structural Equation Modeling Approach to Test the Application of Pfieffer Concept of Strategic Planning on Libyan Universities - Salem Ali Salem Matoug; Mahmoud Mohamed Ali; Asma Abdul Rahman (Elixir International Journal, 2024)
This study examined the relationships between strategic business model, operational plans and big picture and strategic planning process among Libyan students in Malaysia. Data was collected from 204 respondents using structured questionnaire from the selected universities in Malaysia. The descriptive analysis revealed that, majority of the respondents were male who are mostly working in the tertiary institutions in Libya. Pearson correlation analysis using SEM-AMOS have shown a significant positive and high relationship between strategic business model, operational plans and big picture and strategic planning process which means, higher strategic planning process is associated with these three constructs. In line with this finding the authors concluded that, strategic planning based on theory of Pfeiffer is applicable to Libyan universities due to significant and positive relationships between the variables in Pfeiffer’s theory and strategic planning. Thus, the authors recommends that universities, particularly in Libyan should adopt the current approach of strategic planning in order to achieve the set objectives of their universities. Moreover, if this approach is implemented in the universities by the management, it will enhance in managing information and monitoring academic development.